Pengaruh Return On Asset (ROA), Debt To Total Asset (DTA), Cash Ratio, Growth, dan Firm Size Terhadap Kebijakan Dividen - Ronny Malavia Mardani (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2017)
The purpose of this study is to examine the effect of Return on Assets (ROA), Debt to Total Assets (DTA), Cash Ratio, Growth, and Firm Sise on Dividend Policy. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange period 2013-2016. While the sample of the study was determined by using purposive sampling, which obtained a number of 25 companies that qualify as research samples.Based on the analysis results can be seen that the Return on Asset (ROA) have a significant positive effect on dividend policy, Debt to Total Asset (DTA) and Cash Ratio (CR) have no significant positive effect on dividend policy. While Growth and Firm Size have no significant negative effect on dividend policy.